POLA PEMETAAN PENYEBARAN PENYAKIT DEMAM BERDARAH PADA WILAYAH KOTA PALEMBANG - Lastri Widya A; Dhamayanti Dhamayanti (Jurnal Informatika Global)
Palembang region consists of 16 districts, an area that is separated by a large river that divides into two regionsand Ulu Ilir, Palembang, besides most of the region is also an area of swamps. Environmental conditions is very large influence on the spread of dengue fever. The problem faced is the difficulty of mapping the spread of dengue fever that has slowed the anticipation and prevention of dengue fever cases. Needed a pattern that maps the spread of dengue fever by location (region), time, and season. To prevent Extraordinary Events (KLB) and monitor the spread of dengue fever in the region of Palembang in this study carried out to map the spread of dengue fever in the region of Palembang by using the nearest neighbor method.